2015
DOI: 10.1007/s10549-015-3421-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conventional neoadjuvant chemotherapy for breast cancer on tumor angiogenesis

Abstract: The effects of breast cancer conventional chemotherapy on tumor angiogenesis need to be further characterized. Neoadjuvant chemotherapy is an ideal model to evaluate the results of chemotherapy, allowing intra-patient direct comparison of antitumor and antiangiogenic effects. We sought to analyze the effect of neoadjuvant chemotherapy on tumor angiogenesis and its clinical significance in breast cancer. Breast cancer patients (n = 108) treated with neoadjuvant sequential anthracyclines and taxanes were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Some translational studies suggest that vascular characteristics, related to vessel size and morphology, are associated with prognostic differences in breast cancer. Specifically, a higher vascular size and complexity, experimentally linked to thrombospondin and VEGFA changes, seem to confer a worse prognosis in breast cancer, as others and we have shown before [ 9 , 14 ]. In particular, we have previously characterized a bad-prognosis VEGFA-related angiogenic profile characterized by a higher mean vascular size (MVS) and by the presence of glomeruloid microvascular proliferation (GMP), but without increased microvascular density (MVD).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Some translational studies suggest that vascular characteristics, related to vessel size and morphology, are associated with prognostic differences in breast cancer. Specifically, a higher vascular size and complexity, experimentally linked to thrombospondin and VEGFA changes, seem to confer a worse prognosis in breast cancer, as others and we have shown before [ 9 , 14 ]. In particular, we have previously characterized a bad-prognosis VEGFA-related angiogenic profile characterized by a higher mean vascular size (MVS) and by the presence of glomeruloid microvascular proliferation (GMP), but without increased microvascular density (MVD).…”
Section: Introductionsupporting
confidence: 65%
“…Additionally, modulation of tumor angiogenesis by conventional chemotherapy, with potential synergistic and antagonistic effects, further confounds the interpretation of clinical results. In fact, others and we have demonstrated that chemotherapy exerts variable changes in tumor vascular network, which are clearly related neither to pathologic response nor to patients outcome [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…CRCD does not necessarily imply tissue ischemia [ 18 ] and an increase, rather than a decrease, of miR-126-3p concentrations was found after the chemotherapy. As miR-126-3p is enriched in endothelial cells and promotes blood vessels formation [ 39 ], its upregulation could be a response to cellular stress and anti-angiogenic activity of the chemotherapy [ 40 ]. In the same way, miR-199a-3p levels also decreased in acute heart failure [ 41 ], while our results have shown an elevation after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…PDGFA is a well-characterized pro-angiogenic factor in different physiological and pathological conditions including organ development, ischemia and renal diseases [ 34 36 ]. In addition, expression of PDGFA has been shown to be associated with high vascular density, lymph node metastasis and tumor recurrence in breast cancer [ 37 , 38 ]. Our data indicated that PDGFA is a direct target of KDM2A and a critical mediator of KDM2A-induced tube formation of endothelial cells (Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%